Routledge handbook of policy design - Howlett, Michael; Mukherjee, Ishani (Routledge, Taylor & Francis Group, 2018)
Introduction : the importance of policy design : effective processes, tools and outcomes / Michael Howlett and Ishani Mukherjee -- The contexts and components of policy design : governance modes and policy regimes / Michael Howlett -- Designing complex policy mixes : elements, processes and characteristics / Karoline S. Rogge -- The promise of co-design for public policy / Emma Blomkamp -- Policy instruments and policy design choices : selecting substantive and procedural tools in public policymaking / Michael Howlett -- Persuasive systems design : key issues, process model, and system features / Harri Oinas-Kukkonen and Marja Harjumaa -- Aligning policy tools and their targets : nudging and utility maximization in policy design / Michael Howlett -- Design thinking in public policy / Michael Mintrom and Joannah Luetjens -- Understanding policy designs over time : layering, stretching, patching and packaging / Michael Howlett, Ishani Mukherjee, and Jeremy Rayner -- Thinking outside the box? : applying design theory to public policy / Mark Considine -- Perspectives on policy analysis : a framework for understanding and design / Igor S. Mayer, C. Els van Daalen and Pieter W.G. Bots -- Instrument constituencies : promoting policy designs / Jan-Peter Voss and Arno Simons -- Policy design and policy advisory systems / Thurid Hustedt -- Policy design and conflict / Saba Siddiki -- Nudges and nodality tools : new developments in old instruments / Colin R. Kuehnhanss -- Authority tools : pervasive, persistent and powerful / Arie Freiberg -- Treasure tools : a primer on subsidies / Ronald Steenblik -- Designing organizational tools : tool choices as administrative reforms / Per Laegreid -- Digital tools for rapid policy design / Justin Longo -- Policy design and non-design : a continuum of formulation modalities / Michael Howlett and Ishani Mukherjee -- Linking policy design and implementation styles / Jale Tosun and Oliver Treib -- Policy capacity : a design perspective / Azad Singh Bali and M Ramesh -- Crowdsourcing and policy design / Araz Taeihagh -- Capacities and customization in policy design / Ishani Mukherjee and Azad Singh Bali -- Gauging effectiveness : first and second-best policy design / Ishani Mukherjee and Michael Howlett -- Coherence, congruence and consistency in policy mixes / Michael Howlett and Jeremy Rayner -- Managing uncertainty : controlling for conflicts in policy mixes / Pablo del Río -- Agility and robustness as design criteria / Giliberto Capano and J.J. Woo -- How to sequence policies : the PM-ARM approach / Araz Taeihagh.